2010
DOI: 10.1002/ca.20963
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord termination in adult Africans: Relationship with intercristal line and the transumbilical plane

Abstract: The level of cord termination and level of vertebral intersection of intercristal line and transumbilical plane (TUP), frequently used landmarks, show ethnic variation. The relationship of the spinal cord termination to these lines is vital in spinal surgery and anesthesia, but data on these parameters are scarce in the African population. The purpose of this work is to determine the level of cord termination and establish its relationship with intercristal line and TUP. One hundred and twelve specimens obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…A radiographic study in 450 European adult patients showed that the line crossed the body of L4 or the L4/5 intervertebral disc in 72% of cases (Walsh et al, 2006). These findings support a previous radiographic study of 163 patients in which the figure was 79% (Render, 1996) and are similar to subsequent smaller radiographic studies of European (Chakraverty et al, 2007) and American (McGaugh et al, 2007) adults, and a dissection study of African cadavers (Gatonga et al, 2010). The equivalent figure determined by radiography in 72 Korean adults was 64% (Kim et al, 2007), but it is difficult to know whether this is a true ethnic difference.…”
Section: Supracristal Planesupporting
confidence: 85%
See 1 more Smart Citation
“…A radiographic study in 450 European adult patients showed that the line crossed the body of L4 or the L4/5 intervertebral disc in 72% of cases (Walsh et al, 2006). These findings support a previous radiographic study of 163 patients in which the figure was 79% (Render, 1996) and are similar to subsequent smaller radiographic studies of European (Chakraverty et al, 2007) and American (McGaugh et al, 2007) adults, and a dissection study of African cadavers (Gatonga et al, 2010). The equivalent figure determined by radiography in 72 Korean adults was 64% (Kim et al, 2007), but it is difficult to know whether this is a true ethnic difference.…”
Section: Supracristal Planesupporting
confidence: 85%
“…The latter was also confirmed in a recent study of 112 adult cadavers in Kenya (Gatonga et al, 2010). Two of these studies also found that the dural sac terminates at S2 in about two thirds of individuals but may be higher or lower (Macdonald et al, 1999;Soleiman et al, 2005).…”
Section: Termination Of Spinal Cordmentioning
confidence: 53%
“…1 The lowest normal level is considered to be between L2 and L3 intervertebral disk. 4 The aims of present investigation were to determine the level of termination of the CM by reviewing a large series of magnetic resonance (MR) images in Turkish population and correlate this position with sex, height, and weight. 4 The aims of present investigation were to determine the level of termination of the CM by reviewing a large series of magnetic resonance (MR) images in Turkish population and correlate this position with sex, height, and weight.…”
mentioning
confidence: 99%
“…Some reports were described that TLCM was more caudally located in females [1, 8, 9] and the elderly [1] and showed differences between races [10–12]. In addition, previous reports revealed that the presence of spinal deformities and lumbosacral transitional vertebrae were associated with variations in the TLCM [1316].…”
Section: Discussionmentioning
confidence: 99%